Prevalence of depression and its associated factors among medical students in International Islamic University Malaysia (IIUM) - Said, Abdul Hadi; Azmi, Mohd Addin Nur Hakim; Mohd Hanapiah, Haziqah; Abdullah, Anis Wardati; Shalihin, Mohd Shaiful Ehsan (International Islamic University Malaysia, 2021)
INTRODUCTION: Globally, depression is one of the serious problems reported among medical students. Various studies reported that the prevalence of depression among medical students was high due to multiple risk factors. Therefore, this study aimed to measure the prevalence of depression and its associated factors among medical students in International Islamic University Malaysia (IIUM). MATERIALS AND METHODS: A cross-sectional study was conducted among 500 medical students in IIUM Kuantan. A validated self-reported questionnaire using Depression Anxiety Stress Score 21 was distributed during the second semester of the 2018/2019 session. Descriptive statistics were used to measure the prevalence of depression. Chi-square test, Fisher’s exact test, independent sample T-test, and multiple logistic regression were used to determine the association between risk factors and depression. RESULTS: The prevalence of depression was 39% with 10.5% of them having severe and extremely severe levels of depression. Multiple logistic regression analysis showed regular physical activity (AOR=0.64, 95% CI: 0.42-0.98) and Tahajjud prayer practice (AOR: 0.76, 95% CI 0.66-0.88) are two protective factors against depression among medical students. CONCLUSION: : About every two out of five IIUM medical students had depression. Regular physical activity and Tahajjud prayer practiced may reduce the risk of depression and should be encouraged